Association between coronary artery calcium and cardiovascular disease as a supporting cause in cancer: The CAC consortium - Frances M. Wang; Cara Reiter-Brennan; Zeina Dardari; Catherine H. Marshall; Khurram Nasir; Michael D. Miedema; Daniel S. Berman; Alan Rozanski; John A. Rumberger; Matthew J. Budoff; Omar Dzaye; Michael J. Blaha (Elsevier, 2020)
Background: Identifying cancer patients at high risk of CVD is important for targeting CVD prevention strategies and evaluating chemotherapy options in the context of cardiotoxicity. Coronary artery calcium (CAC), a strong marker of coronary atherosclerosis, is used clinically to enhance risk assessment, yet the value of CAC for assessing risk of CVD complications in cancer is poorly understood. Objective: In cases of cancer mortality, to determine the value of CAC for predicting risk of CVD as a supporting cause of death. Methods: The CAC Consortium is a multi-center cohort of 66,636 asymptomatic adults without CVD who underwent CAC scanning. During a follow-up of 12.5 years, 1129 patients died of cancer and were included in this analysis. The primary outcome was presence of CVD listed as a supporting cause of cancer mortality on official death certificates obtained from the National Death Index. Logistic regression models were used to assess the odds of CVD being listed as a supporting cause of death by CAC. Results: CVD was listed as a supporting cause of death in 306 (27%) cancer mortality cases. Baseline CAC was significantly higher in individuals with CVD-supported mortality. Odds ratios of having CVD-supported death increased by ASCVD risk score category [1.15 (0.81, 1.65) for 5-20% 10-year risk and 1.97 (1.36, 2.89) for ≥20% risk, in reference to <5% 10-year ASCVD risk] and CAC category [1.07 (0.73, 1.57) for CAC 1-99, 1.29 (0.87, 1.93) for CAC 100-399, and 2.14 (1.48, 3.09) for CAC ≥400 relative to CAC 0]. In the CAC ≥400 group, these associations remained significantly elevated after adjustment for traditional CVD risk factors [1.66 (1.08, 2.55)]. A sensitivity analysis using a more specific ASCVD-supported mortality outcome, defined as coronary heart disease, stroke, and peripheral artery disease, demonstrated that adjusted odds of ASCVD-supported cancer mortality were significantly elevated in the CAC ≥400 group relative to CAC 0 [3.09 (1.39, 7.38)]. Conclusions: In cancer mortality cases, high antecedent CAC predicted risk of having CVD as a supporting cause of death on official death certificates, independently of ASCVD risk score and CVD risk factors. CAC may be useful for identifying cancer patients at high CVD risk who might benefit from more intense preventive cardiovascular therapies.